2005
DOI: 10.1016/j.quascirev.2004.07.018
|View full text |Cite
|
Sign up to set email alerts
|

New data for Late Pleistocene Pinedale alpine glaciation from southwestern Colorado

Abstract: New cosmogenic surface-exposure ages of moraine-crest boulders from southwestern Colorado are compared with published surface-exposure ages of boulders from moraine complexes in north-central Colorado and in west-central (Fremont Lake basin) Wyoming.10 Be data sets from the three areas were scaled to a single 10 Be production rate of 5.4 at/g/yr at sea level and high latitude (SLHL), which represents the average 10 Be production rate for two high-altitude, mid-latitude sites in the western United States (US) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 34 publications
4
75
0
Order By: Relevance
“…36 Cl ages from LLGM moraines at Hogback Mountains on the eastern side of the San Juan Mountains (Fig. 3, site C) suggest that post-LLGM recession may have begun there as late as 17.5 ka (Benson et al, 2005). Those ages are not, however, recalculated with more recent production rates, and are likely too young compared to the recalculated 10 Be ages.…”
Section: Chronology Of the Llgm And The Initiation Of Deglaciation Inmentioning
confidence: 98%
See 3 more Smart Citations
“…36 Cl ages from LLGM moraines at Hogback Mountains on the eastern side of the San Juan Mountains (Fig. 3, site C) suggest that post-LLGM recession may have begun there as late as 17.5 ka (Benson et al, 2005). Those ages are not, however, recalculated with more recent production rates, and are likely too young compared to the recalculated 10 Be ages.…”
Section: Chronology Of the Llgm And The Initiation Of Deglaciation Inmentioning
confidence: 98%
“…The two uncertainties are summed in quadrature to produce an estimate of uncertainty of the reported mean age. To insure consistency across studies, for studies where authors have presented multiple interpretations of CRN ages depending on post-depositional erosion and shielding assumptions (e.g., Benson et al, 2004Benson et al, , 2005Benson et al, , 2007Brugger, 2007), we utilize the values reported assuming zero-erosion/zero-shielding histories.…”
Section: Interpretation Of Moraine-boulder Crn Surface-exposure Agesmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory and procedures for 10 Be age determinations are the same as those in Benson et al (2005). The chemical and isotopic ratios used in the calculation of surfaceexposure ages are given in Table 3.…”
Section: Be Determinationsmentioning
confidence: 99%